Effect of Cyclic Loading on the Fixture-Abutment Microgap in Short Implants Versus Standard Implants: An In Vitro Study - Gholamreza Esfahanizadeh; Ezatollah Jalalian; Seyyede Niloufar Salehi; Mahsa Ghasemi; Shaghayegh Golalipour (International Journal of Dentistry)
Conclusion: Cyclic loading increased the amount of fixture-abutment microgap in both the standard and short implants. However, the difference in this respect was not significant between the two implant lengths. Thus, short implants could be reliably used in patients with limitations for surgery to restore function and esthetics.